What is `int x*e^(-x^2) dx`

Asked on by agnesha

2 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

We have to find the value of : `int x*e^(-x^2) dx`

Let -x^2 = y

dy/dx = -2x

x*dx = (-1/2)*dy

`int x*e^(-x^2) dx`

=> `int (-1/2)*e^y dy`

=> `(-1/2)*e^y`

substitute y = -x^2

=> `-1/(2*e^(x^2))`

The required integral is `-1/(2*e^(x^2))`

oldnick's profile pic

oldnick | (Level 1) Valedictorian

Posted on

`int xe^(-x^2) dx= -1/2 int -2xe^(-x^2) dx= -1/2 int d e^(-x^2)=-1/2 e^(-x^2)`

We’ve answered 320,004 questions. We can answer yours, too.

Ask a question